Reconstruction of the Legal Governance of Customary Tourism Villages: Addressing Institutional Fragmentation in Indigenous-Based Tourism Development - Hariri, Achmad Hariri; Babussalam, Basuki (International Journal of Educational Research & Social Sciences, 2026)
This study examines the reconstruction of the legal governance of customary tourism villages in addressing institutional fragmentation within indigenous-based tourism development. The research is motivated by the persistent gap between normative legal frameworks and practical implementation, particularly due to regulatory fragmentation, weak recognition of indigenous rights, unequal power relations, and the absence of fair benefit-sharing mechanisms. Using a normative legal research method with statute and conceptual approaches, this study analyzes the disharmony among regulations related to village governance, tourism, and indigenous peoples, as well as relevant theoretical frameworks such as legal pluralism, legal recognition, and collaborative governance. The findings indicate that existing governance models remain sectoral, state-centric, and insufficiently integrative, resulting in legal uncertainty and limited participation of indigenous communities. As a solution, this study proposes a legal reconstruction based on the Quadruple Helix model, which integrates government, academia, the private sector, and indigenous civil society into a collaborative and participatory governance system. This model emphasizes co-design, co-governance, and rights-based approaches to ensure inclusivity, accountability, and equitable distribution of benefits. In conclusion, the reconstruction of legal governance requires strengthening legal substance, institutional design, and legal culture to create an integrated, sustainable, and socially just framework for customary tourism village development, with indigenous communities as the primary subjects